Working conditions, authorizations, mental health, and job satisfaction of physician assistants in Germany - Treusch, Yvonne; Möckel, Luis; Kohlstedt, Karin (Frontiers in Public Health, 2023)
Objective: This study explores associations between overall and facet-specific job satisfaction, work-related factors, responsibilities and mental health of physician assistants (PAs) in Germany, in order to identify factors that prolong lifetime and well-being of PAs in practice and to counteract shortage of health care stuff. Methods: An online survey comprising sociodemographic and work-related items, items from the short questionnaire of general and facet-specific job satisfaction (KAFA) and the Depression, Anxiety and Stress Scale (DASS-21) were distributed to PAs working in Germany in 2021 (cross-sectional survey design). Descriptive statistics, DASS-21 subscale score analysis, T-test, ANOVA or Kruska-Wallis test were used. Results: PAs (n=169) were working mainly in surgery (23.2%), internal medicine (20.3%) or orthopedics and trauma surgery (17.5%), whereas only few PAs were working in emergency care, geriatrics, neurology or oncology. They were responsible for a broad spectrum of medical activities depending on practice setting. PAs working in emergency care claimed to be the most empowered, followed by PAs in orthopedics and surgery. Almost all PAs carried out documentation, anamnesis and diagnostic services. Although almost all PAs rated their overall job satisfaction as good, satisfactory or pleasant (91.6%), single facets of job satisfaction were rated differently. Colleagues and supervisors were assessed very positive, whereas payment, professional activities were rated rather average and development opportunities even worse. PAs working in oncology demonstrated the highest overall job satisfaction, followed by PAs working in geriatrics and emergency care. Overall job satisfaction was significantly negatively associated with depression, anxiety and stress scores (p≤0.001, p≤0.05, p≤0.05, respectively). Particularly, female, urban and PAs working in oncology demonstrated significantly increased anxiety scores. Moreover, depression scores of PAs working in oncology or neurology or with a low net income exceeded critical cut off values. Conclusions: Interventions aiming at removing the significant negative correlation between job satisfaction, depression, anxiety and stress scores are needed. To retain PAs in job, salary, autonomy and development opportunities should be improved and prevention programs for anxiety and depression should be offered. Remarkably, PAs overall good job satisfaction was mainly determined by good evaluation of supervisors and colleagues.